Pendampingan pastoral dan kesehatan mental: Sebuah ikhtiar integratif dalam perspektif Alfred Adler - Poluan, Alvonce; Nugroho, Fibry Jati (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
Amid the global mental health crisis, conventional psychotherapy often fails to address the spiritual-existential dimensions of humanity. This study constructs an integrative Pastoral-Adlerian model that bridges Alfred Adler's individual psychology and pastoral theology to provide holistic mental health services. Through a critical literature review, the research synthesizes Adler's concepts—inferiority complex, teleology, and social interest—with Christian theological principles of grace, imago Dei, and vocation. Analysis reveals substantial compatibility: feelings of inferiority are reframed as spaces in which grace operates, while social interest manifests as the restoration of God's image. The model formulates four cyclical transformative stages: building empathic relationships, exploring life narratives, reorienting meaning and purpose, and community reintegration. This Pastoral-Adlerian integration signifies an ethical approach to comprehensively heal injured humanity, converting counseling environments into sanctuaries where faith and psychology collaborate to restore human dignity. Abstrak Di tengah krisis kesehatan mental global, psikoterapi konvensional sering gagal menyentuh dimensi spiritual-eksistensial manusia. Penelitian ini mengonstruksi model integratif Pastoral-Adlerian yang menjembatani psikologi individual Alfred Adler dengan teologi pastoral untuk menghadirkan layanan kesehatan jiwa holistik. Melalui studi pustaka kritis, penelitian mensintesiskan konsep Adler—inferiority complex, teleologi, dan social interest—dengan prinsip teologi Kristen tentang anugerah, imago Dei, dan panggilan hidup. Hasil analisis menunjukkan kompatibilitas substantif: perasaan inferioritas dimaknai sebagai ruang bagi kasih karunia, sementara kepedulian sosial sebagai pemulihan gambar Allah. Model ini diformulasikan dalam empat tahapan siklik: membangun relasi empatik, eksplorasi narasi hidup, reorientasi makna tujuan, dan reintegrasi komunitas. Integrasi ini merupakan respons etis untuk merawat kemanusiaan yang terluka secara utuh.